In vivo reliability of 3D cephalometric landmark determination on magnetic resonance imaging: a feasibility study - Jürchott, Alexander; Freudlsperger, Christian; Zingler, Sebastian; Saleem, Muhammad Abdullah; Jende, Johann; Lux, Christopher J.; Bendszus, Martin; Heiland, Sabine; Hilgenfeld, Tim (Clinical oral investigations, 2020)
3D cephalometric analysis performed on cone-beam or multi-slice computed tomography (CBCT, MSCT) has superior diagnostic value compared to 2D cephalometry based on radiographs. However, this comes at the expense of increased radiation risks for the predominantly young patients. Magnetic resonance imaging (MRI) has the potential to overcome this diagnostic dilemma but has not been established for 3D cephalometry so far. Since landmark reliability forms the basis for 3D cephalometry, we evaluated the in vivo reliability of established 3D landmarks using MRI. Sixteen orthodontic patients underwent MRI at 3 Tesla using a 0.5 mm 3D sequence. On each MRI scan, 44 cephalometric landmarks were determined. Image analysis was performed twice by two independent observers. Intra- and inter-rater agreement was assessed by mean measurement errors and intraclass correlation coefficients (ICCs). Measurement errors were calculated as Euclidean distances and distances for x-, y-, and z-coordinates. Overall, MRI-based 3D cephalometric landmarks revealed a high reliability comparable to prior in vivo studies using CBCT/MSCT. Intra- and inter-rater ICCs were consistently higher than 0.9. Intra-rater comparisons showed mean measurement differences (ranges) of 0.87 mm (0.41-1.63) for rater I and 0.94 mm (0.49-1.28) for rater II. Average inter-rater difference was 1.10 mm (0.52-2.29). Distinct differences in reliability between the various landmarks were observed, corresponding well with the landmarks’ specific shapes. The present study demonstrates that MRI enables reliable determination of 3D cephalometric landmarks in vivo. This study emphasizes the potential of MRI to perform treatment planning and monitoring in orthodontics as well as oral and maxillofacial surgery without radiation exposure.